Subjective well-being, self-actualization characteristics, and coping strategies of Russian railroad employees with different positions - E. F. Yashchenko; E. G. Shchelokova (Вестник университета, 2025)
A review of modern Russian and foreign scientific publications considering subjective well-being as a factor of economic effect ensuring safety of the ergatic system has been presented, which allows us to substantiate the relevance of the research topic. The purpose of the study is to determine the features of subjective well-being, self-actualization and personality characteristics, and coping strategies in railroad employees with different job positions such as train managers and train drivers. The study sample consisted of 39 railroad employees with higher education, average age 35.90 years, of whom 22 were train managers and 17 were train drivers. The samples were homogeneous by gender (all men) and level of education (higher education). The research methods were the Scale of subjective well-being by A. Perrudet-Badoux, G. Mendelsohn, and J. Chiche in M.V. Sokolova’s adaptation, E. Shostrom’s self-actualization test in adapted Yu.E. Aleshina, L.Y. Gozman, M.V. Zagik, and M.V. Kroz, R. Lazarus’ coping test adapted by T.L. Kryukova, E.V. Kuftyak, and M.S. Zamyshlyaeva, and I.L. Solomin’s personality type self-assessment questionnaire. Psychological portraits of railroad employees with different job positions have been compiled. Differences and connections among the studied phenomena in train managers and train drivers have been described. Significant qualities and sources of personal growth for both groups have been shown, and suggestions for further research have been made.